Case Report: Eosinophilic Bronchiolitis With Eosinophil ETosis in Mucus Plugs Successfully Treated With Benralizumab - Sasaki, Hisashi; Miyata, Jun; Irie, Akiko; Kuwata, Ayako; Kouzaki, Yuji; Ueki, Shigeharu; Kawana, Akihiko (Frontiers in Pharmacology, 2022)
Eosinophilic bronchiolitis is a rare allergic disorder caused by eosinophilic inflammation in the bronchioles of the lungs. An effective treatment strategy is needed in cases resistant to steroids. However, its pathophysiology remains unclear owing to the limited number of cases. We herein present the case of a 31-year-old man who experienced eosinophilic bronchiolitis with eosinophil ETosis (EETosis) in the mucus plugs. The patient was diagnosed with asthma. His respiratory symptoms worsened with eosinophilia when treated with the standard asthma regimen, including inhaled corticosteroids, long-acting β2-agonist, long-acting muscarinic antagonist, and leukotriene receptor antagonist. Chest computed tomography revealed bronchial wall thickening and centrilobular nodules in the lower lobes of both lungs. Bronchoscopy showed obstruction of the subsegmental bronchus with mucus plugs. Histological analysis demonstrated abundant eosinophils in the mucus plugs. Cytolytic eosinophils together with Charcot–Leyden crystal formations and deposition of major basic proteins were also observed, indicating the occurrence of EETosis. Introduction of benralizumab, an anti-interleukin-5 receptor α antibody, successfully controlled the patient’s condition and reduced the amount of systemic corticosteroids administered. Our findings confirm that this antibody strongly decreases airway eosinophils in patients with severe asthma. Thus, benralizumab might be an optimal therapeutic agent for the treatment of mucus plug-forming and/or EETosis-occurring eosinophilic lung diseases, including eosinophilic bronchiolitis.